PECULIARITIES OF ENSURING THE ECONOMIC SECURITY OF THE STATE - POPOVYCH, Rostyslav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This study presents a comprehensive approach to analyzing the state’s economic security as a key component of national security, ensuring the stability and resilience of the economic system in the face of global challenges. The work examines major aspects of economic security, such as financial, social, energy, digital, and environmental security, and their role in ensuring the state’s and its regions’ sustainable development. The literature review demonstrates that financial stability and diversification of income sources are crucial components of economic security, enabling the state to counter external and internal threats effectively. Particular attention is given to the issues of digitalization and its impact on economic security in the context of the growing global information society. Implementing digital technologies increases management efficiency and facilitates a rapid response to threats and ensures transparency in decision-making. However, digitalization brings new risks associated with cybersecurity and the need for regulatory oversight. The study also emphasizes the importance of energy independence, which is a critical factor for national security. Diversification of energy sources, development of a domestic energy infrastructure, and energy-saving policies help reduce dependence on external suppliers and ensure economic stability in times of energy crises. Social and environmental security are viewed as foundations for achieving stable economic growth. A high level of social security helps reduce social tensions and improve the quality of life, positively impacting economic development. At the same time, environmental security guarantees the sustainable use of natural resources and environmental protection, which is crucial for sustainable development and public health. The study’s conclusions highlight the necessity of an integrated approach to ensuring economic security in Ukraine. Continued investment in digital technologies, environmental initiatives, social support, and energy independence is recommended to strengthen economic resilience and reduce vulnerability to external threats.